Application of ecosystem service flows model in water security assessment: A case study in Weihe River Basin, China - Cheng Zhang (Elsevier, 2021)
Assessing water resource security is vital for the environment development. However, most studies only focus on the static water security status of the region, ignored the spatial flows of ecosystem services. Whereas by integrating the ecosystem services flows model into water security simulation, that we could provide scientific reference for achieving the local water resources sustainable development, and making effective ecological compensation policy. In our study, ecosystem service flows model was integrated into water security assessment to simulate the spatial patterns of water security in Weihe River Basin (WRB) from 2005 to 2015. The results show that (1) the contradiction between the supply and demand of water resources in WRB was prominent, due to the upstream water resources supply, the areas which achieve water security accounted for 10.89% each year. Furthermore, the insufficient and unsupplied areas were increased, which was adverse to the sustainable development of the river basin. (2) The water security index (WSI) in WRB was the lowest in 2010, and the highest in 2005. The change of regional WSI was influenced by the nature environment and human beings, and the main factors were agricultural water consumption and population. (3) The spatial heterogeneity of agricultural water consumption was diverse in the whole river basin, the agricultural water-use efficiency in Weinan City was lower, while the per residential domestic water in Xi’an and Xianyang city was much higher. Therefore local government should advocate develop water-saving agriculture and control urban water quotas, moreover, by adjusting water price cost and raise raising residents' human awareness of water-saving so as to improve the water security in the river basin. This study could provide a theoretical basis for the sustainable development of regional water resources and the promoting the mechanism of ecological compensation.